The Effects of Houttuyniae Herba extract on the Activity of Anti-bacteria, Anti-inflammation and Anti-oxidation - Oh-do Jeon; Hyeong-sik Seo (Journal of Pharmacopuncture, 2008)
Objective : This experimental study was performed to investigate the effects of Houttuyniae Herba extract on anti-inflammation and anti-oxidation. Methods : The cytotoxicity of Houttuyniae Herba water extract and ethanol extract about viability of Raw 264.7 cell were tested using a colormetric tetrazolium assay(MTT assay). We investigated the inhibitory effects of Houttuyniae Herba water extract and ethanol extract on Propionibactrium acnes using paper disk diffusion method. To investigate the antiinflammation effects of Houttuyniae Herba water extract and ethanol extract on LPS-induced macrophage Raw 264.7 cell, we used ELISA kit. We evaluated anti-oxidation effects of Houttuyniae Herba water extract and ethanol extract on HaCaT cell by Enzyme recycling method. Results : 1. In Houttuyniae Herba water extract and ethanol extract, cell toxicity depended on the density and wasn't difference between two extracts. 2. Houttuyniae Herba water extract and ethanol extract has not the significant inhibition effect of Propionibactrium acnes. 3. Concentration of 50, 100㎍/㎖ Houttuyniae Herba water extract inhibited the production of NO in the Raw 264.7 cell stimulated with LPS. 4. All extracts except for 20㎍/㎖ Houttuyniae Herba water extract showed anti-oxidation effect by decreasing the DPPH radicals. Conclusion : These results indicate that Houttuyniae Herba extract has anti-inflammation and anti-oxidation effects. If further study is performed, the use of Houttuyniae Herba extract will be valuable and benificial in the therapy of Propionibactrium acnes.